Measuring radiation exposure to newborns from X-rays in a developing country's NICU - Rakotsoane, D M (My University, 2016)
Background: Radiological studies continue to form part of an important management tool in the Neonatal unit; with advances in technologies extremely premature infants are being ventilated even in resource poor settings with high patient turnover and crowded incubators. At this critical stage of development, a hypothetical question can be asked “Are these vulnerable infants exposed to acceptable levels of radiation?” This study was conducted to measure radiation doses received by these infants from X-rays (primary and scatter beams) in a crowded NICU using Thermoluminescent Dosimeters (TLD). Methodology: This was a prospective descriptive cross sectional study conducted at Chris Hani Baragwanath Academic Hospital recording doses from X-rays performed over a one month period in 2013 in all neonates admitted to NICU. Results: The study population comprised of 47 patients, of which 29 (61.7%) were in the very low birth weight (VLBW) and extreme low birth weight (ELBW) category, 8 (17%) low birth weight infants and 10 (21.3%) term infants. The majority of neonates were admitted for Respiratory distress syndrome (54.6%), followed by Meconium aspiration syndrome (14.7%). Congenital pneumonia and surgical conditions made up (31.6%) of the total NICU admissions. In two months, October and November, 310 X-rays were performed in the NICU. Chest X-rays were the most requested procedure. The mean number of X-rays performed per patient was 8 and the maximum number of X-rays performed on a single patient was 28. Readings from six TLD measuring doses from chest X-ray and abdominal X-rays ranged between 0.005 to 0.08 milliSievert (mSv) per X-ray performed, whilst the reading from three TLD measuring scatter doses ranged between 50 to 150 cm, from the focal point measured 0.0004 mSv per X-ray at 50 and 100cm and zero at 150cm. Conclusion: Our study population had on average 8 X-rays during their stay in NICU, with a mean stay of 10 days. The measured doses on some TLDs were comparable to adult doses per X-ray, which is unacceptably high. Combined with scatter doses, patients admitted in beds (1 to 6) and (9 to 12), could have a higher cumulative dose as the distance between the beds was less than 1.5 meters. Possible reasons for the high doses in this ICU setting could be the parameters used to acquire X-ray, such as focal film distance (FFD), kiloVoltage (kV) showed deviation from the recommended guidelines according to the European Commission Quality criteria for diagnostic radiographic images in pediatrics. This may be related to an absence of local guidelines for radiographic parameters to be used in each weight band. Another reason may be the use of old overhead warmers which were not height adjustable, affecting the focal film distance achievable.
DISSERTATION SUBMITTED IN PARTIAL FULLFILMENT OF REQUIREMENTS FOR A MASTER OF MEDICINE IN PAEDIATRICS AND CHILD HEALTH (MMED PAEDS)